Penyuluhan untuk Meningkatkan Pengetahuan Ibu Rumah Tangga terhadap Pemanfaatan Pangan Lokal Karawang (Terubuk) dalam Pembuatan Cemilan Mudah dan Murah: Counseling to Increase Public Knowledge of the Use of Local Food Karawang (Terubuk) in Making Easy and Cheap Snacks - Milliyantri Elvandari; Risma Rahmatunisa; Sabrina Sabrina (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Terubuk or Saccharum edule Hassk is one of the indigenous vegetables and is native to Southeast Asia. Terubuk has the potential to be developed and can increase its economic value. However, so far, its utilization has not been maximized and is still limited to simple processing techniques such as making fresh vegetables, steaming, sautéing, lodeh vegetables, curry mixture, tamarind vegetables, fried, and used as animal feed so that it is necessary to diversify with more modern and practical processing technology. This community service activity aims to increase homemakers' knowledge about using local food in Karawang, especially terubuk. The method used in this activity is public education through lectures, questions and answers, and discussions. The participants of this activity were Kosambi housewives totaling 16 people. The results of the service there is an increase in the percentage of pre-post test knowledge. Increased knowledge of homemakers can be used as a community empowerment model in increasing knowledge of making healthy, easy, and inexpensive snacks.